Influence of 3d-printing parameters on the mechanical properties of 17-4PH stainless steel produced through Selective Laser Melting (Fracture and Structural Integrity, 2021)
Additive Manufacturing (AM) is a technological process in which elements are fruitfully built up adding materials layer by layer. AM had a massive development in recent times, thanks to its intrinsic advantages, especially if compared with conventional processes (i.e. subtractive manufacturing methods), in terms of free-form design, high customization of products, a significant reduction in raw materials consumption, low request of postprocessing and heat treatments, use of pure materials and reduced time for final products to be marketed. In order to give an innovative contribution to the knowledge in the field of metal AM materials, this paper reports the main outcomes of an experimental campaign focused on the influence of several specific printing parameters on the mechanical features of the 17-4PH stainless steel, which is one of the most used metal for the Selective Laser Melting (SLM) technology. The influence of different printing directions and sample inclinations on the material mechanical behavior is assessed, with the aim of considering an innovative use in the field of structural engineering. Moreover, the effects due to scanning and recoating times are studied. In addition, the consequences of heat treatment (annealing) on both the residual stresses and the amount of residual austenite are appraised.
Keywords: Selective Laser Melting (SLM); 17-4PH stainless steel; Tensile test; 3d-printing parameters; Mechanical properties; Additive Manufacturing